The Alternative Report of Africa (AROA) An African project under construction - (:unkn) unknown (My University, 2021)
AROA proposes a philosophical, ideological and methodological reversal of the usual economic and statistical analyses. International experts still have knowledge based on the values they have been taught in the past and which they constantly reproduce. The statistical methods that underlie economic and political decisions only take into account market values, which are subject to manipulation that influences all economic agents. The famous catching up of development in stages is only a delusion at a time in history when great environmental and human damage has been committed by the economic actors of a greedy capitalism that is not interested in the living conditions of people or their survival. Under these conditions, Africa must build its own instruments to measure the progress of its national economies against the needs of its people and citizens.
Keywords: African Research